Digitalization, Change in Skill Distance between Occupations and Worker Mobility: A Gravity Model Approach - Arnaud Dupuy; Morgan Raux; Sara Signorelli (Institute of Labor Economics (IZA), 2024)
The recent digital revolution has significantly broadened the scope of IT-related tasks in most occupations in the labor market. In this paper, we document these changes, we propose a novel conceptual framework for thinking about the effect of technological change that incorporates the changing task distance between occupations, and we investigate its impact on worker mobility using a gravity equation approach. Our results reveal that the evolution of skill distance between jobs significantly affected mobility patterns, disproportionately favoring workers with preexisting knowledge of digital tools. Finally, we micro-found our gravity equation through a matching model to evaluate mobility in counterfactual scenarios without technological change.
Keywords: J23; J24; J62; 330; occupation mobility; technological change; search and matching